Pengaruh Likuiditas, Profitabilitas, dan Kebijakan Deviden Terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Food And Baverage yang Terdaftar di Bursa Efek Indonesia - Meliana Herwanti; Sri Hermuningsih; Alfiatul Maulida (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of this research is to examine and analyze the factors that influence the firm value. The independent variables in this study are liquidity, profitability, and dividend policy. The population in this study aremanufacturing food and beverage companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sample selection technique used in this study is purposive sampling and has obtained as many as 8 samples of companies with a period of 5 years so that 40 samples of companies were obtained. The analytical method used in this research is multiple regression. The results of this study simultaneously show that liquidity, profitability, and dividend policy have a significant effect on firm value. The results of the study partially show that liquidity has a negative and significant effect on firm value, profitability has a positive and significant effect on firm value, and dividend policy has a negative but not significant effect on firm value.